2015
DOI: 10.1002/tox.22158
|View full text |Cite
|
Sign up to set email alerts
|

17β‐Trenbolone exposure programs metabolic dysfunction in larval medaka

Abstract: Here, we used physiological and transcriptomic analyses to evaluate the effects of 17β-trenbolone (TB) on metabolism during the early life stage of medaka (Oryzias latipes). In the physiological experiments, sex reversal rates increased continuously in proportion to TB concentrations (2-100 ng/L), and were 100% (all males) in the 200 ng/L treatment group. TB caused a significant increase in the gonadosomatic index of females at concentrations of 60 and 100 ng/L. These females exhibited swollen abdomens and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Production of phenotypic males was more sensitive in zebrafish (100% males at 0.05 μg/L) compared with medaka (no effect at 0.05 μg/L). Mizukami‐Murata et al () confirmed in a developmental study (exposure 0–60 d post fertilization) the relative insensitivity of Japanese medaka, with phenotypic masculinization occurring only at concentrations >0.1 μg 17β‐trenbolone/L. The enhanced sensitivity to 17β‐trenbolone during sex differentiation in zebrafish could be a consequence of the extended period of juvenile hermaphroditism that occurs in this species compared with medaka.…”
Section: Summary Of Available Literaturementioning
confidence: 84%
See 2 more Smart Citations
“…Production of phenotypic males was more sensitive in zebrafish (100% males at 0.05 μg/L) compared with medaka (no effect at 0.05 μg/L). Mizukami‐Murata et al () confirmed in a developmental study (exposure 0–60 d post fertilization) the relative insensitivity of Japanese medaka, with phenotypic masculinization occurring only at concentrations >0.1 μg 17β‐trenbolone/L. The enhanced sensitivity to 17β‐trenbolone during sex differentiation in zebrafish could be a consequence of the extended period of juvenile hermaphroditism that occurs in this species compared with medaka.…”
Section: Summary Of Available Literaturementioning
confidence: 84%
“…A number of studies have evaluated changes in gene expression in 17β‐trenbolone‐exposed fish at different life stages, using both targeted (polymerase chain reaction [PCR]) and nontargeted (e.g., microarray) techniques (Hook et al ; Garcia‐Reyero et al ; Dorts et al ; Ekman et al ; Brockmeier et al ; Leet et al ; Mizukami‐Murata et al ). For example, Leet et al () observed down‐regulation of several genes involved in steroid synthesis in larval fathead minnows exposed to 17β‐trenbolone, consistent with a compensatory response to overstimulation of the HPG axis by exogenous steroids.…”
Section: Summary Of Available Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish ( Danio rerio ) exposed to trenbolone (TRB) during sexual differentiation develop skewed sex ratios and all male populations at 0.01 μg/L and above ( Larsen and Baatrup 2010 ; Morthorst et al 2010 ; Boettcher 2011 ; Baumann et al 2015 ) this phenotypic sex change is irreversible ( Larsen and Baatrup 2010 ; Morthorst et al 2010 ; Baumann et al 2015 ). The TRB-induced reversal to a male phenotype appears more sensitive in zebrafish than in medaka ( Örn et al 2006 ; Mizukami-Murata et al 2015 ). Other endocrine mechanisms can also lead to masculinisation in fish (for a review see Matthiessen and Weltje 2015 ).…”
Section: Delayed Effectsmentioning
confidence: 99%
“…However, there are no reports on body burden of 17β‐trenbolone in birds in the environment. Whereas effects of 17β‐trenbolone have been well characterized in fish (Ankley et al 2003; Ekman et al 2011; Mizukami‐Murata et al 2016), there have been few studies in avian species, primarily using Japanese quail ( Coturnix japonica ; Quinn et al 2007a; Henry et al 2012; Karouna‐Renier et al 2017). Similar to results in fish, these studies also demonstrated deleterious effects on plasma hormone levels and reproductive behavior, as well as decreased egg production.…”
Section: Introductionmentioning
confidence: 99%